Sovereign Debt Restructurings in Grenada : Causes, Processes, Outcomes, and Lessons Learned - Asonuma, Tamon (IMF Working Papers; Working Paper, 2017)
This paper documents the two debt restructurings that Grenada undertook in 2004-06 and 2013-15.Both restructurings emerged as a consequence of weak fiscal and debt situations, whichbecame unsustainable soon after external shocks hit the island economy. The two restructurings provided liquidity relief, with the second one involving a principal haircut. However, the first restructuring was not able to secure long-term debt sustainability. Grenada's restructuring experience shows the importance of (1) establishing appropriate debt restructuring objectives; (2) committing to policy reforms and maintaining ownership of the restructuring goals; and (3) engaging closely and having clear communications with creditors.